Causes, consequences, and perspectives in the variations of intestinal density of colonization of multidrug-resistant enterobacteria - RUPPE, ETIENNE; Andremont, Antoine (Frontiers in Microbiology, 2013)
The intestinal microbiota is a complex environment that hosts 1013 to 1014 bacteria. Among these bacteria stand multidrug-resistant enterobacteria, which intestinal densities can substantially vary, especially according to antibiotic exposure. The intestinal density of multidrug-resistant enterobacteria and their relative abundance (i.e. the proportion between the density of multidrug-resistant enterobacteria and the density of total enterobacteria) could play a major role in the infection process or patient-to-patient transmission. This review discusses the recent advances in understanding (i) what causes variations in the density or relative abundance of intestinal colonization, (ii) what are the clinical consequences of these variations and (iii) what are the perspectives for maintaining these markers at low levels.